2004
DOI: 10.3171/spi.2004.100.4.0317
|View full text |Cite
|
Sign up to set email alerts
|

Outcome evaluation of the operative management of lumbar disc herniation causing sciatica

Abstract: Object. The authors conducted a study to assess health-related quality of life (HRQOL) and the appropriateness of surgery in patients who have undergone elective lumbar discectomy. Methods. The study involved a prospective cohort of 82 surgically treated patients with lumbar disc herniation causing lower-extremity radiculopathy. An independent study coordinator recorded demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
5
28
0
5
Order By: Relevance
“…In the 43 patients who underwent surgery within 60 days following the onset of their symptoms, HRQOL scores were greater (0.08 compared with 0.05), QALYs were greater (2.50 compared with 1.64), and cost per QALY was less (€1351 compared with €2182) compared with the 58 patients who waited longer than 60 days for surgery 5. Fisher et al prospectively studied 82 patients with lumbar disk herniation with radiculopathy and found that patients who had surgery within 3 months of symptom onset had better HRQOL scores (based on the North American Spine Society instruments Neurogenic Symptoms Score and Pain/Disability Score and Short Form-36) compared with patients who were operated on later after symptom onset (following 3.1 to 6 months, 6.1 to 9 months, or 9.1 to 12 months) 13. However, Akagi and colleagues retrospectively studied 46 patients who had surgery for lumbar disk herniation before or after 3 months of symptom duration and found that there were no differences in pain or functional status based on the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire 14.…”
Section: Resultsmentioning
confidence: 99%
“…In the 43 patients who underwent surgery within 60 days following the onset of their symptoms, HRQOL scores were greater (0.08 compared with 0.05), QALYs were greater (2.50 compared with 1.64), and cost per QALY was less (€1351 compared with €2182) compared with the 58 patients who waited longer than 60 days for surgery 5. Fisher et al prospectively studied 82 patients with lumbar disk herniation with radiculopathy and found that patients who had surgery within 3 months of symptom onset had better HRQOL scores (based on the North American Spine Society instruments Neurogenic Symptoms Score and Pain/Disability Score and Short Form-36) compared with patients who were operated on later after symptom onset (following 3.1 to 6 months, 6.1 to 9 months, or 9.1 to 12 months) 13. However, Akagi and colleagues retrospectively studied 46 patients who had surgery for lumbar disk herniation before or after 3 months of symptom duration and found that there were no differences in pain or functional status based on the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire 14.…”
Section: Resultsmentioning
confidence: 99%
“…The patients remained at the hospital for 5 days. 2,3,8,9,[11][12][13][14][15][16] The study population had a mean age of 40 years (range 18 -66), and 68 (46%) of the patients were women. Sixty-six (45%) patients underwent surgery at the L4 -L5 level and 82 (55%) at the L5-S1 level.…”
Section: Methodsmentioning
confidence: 99%
“…In general, preoperative disability and surgical outcomes have been assessed by severity of pain, general health status, and return to work. [1][2][3] There is a paucity of information regarding quality of sexual activities before and after surgical treatment of lumbar disc herniation. Patients and health care professionals often hesitate to talk about the effects of disease, illness, or surgery on sexuality, but it is imperative that sexuality issues be addressed.…”
mentioning
confidence: 99%